Fibroblast Growth Factor Receptor (FGFR) Signaling Pathway in Tumor - Holzmann, Klaus; Marian, Brigitte (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Fibroblast growth factor (FGF) signal transmission has an essential function in embryonic development and tissue repair, and is dysregulated in the vast majority of malignancies studied. The FGF signaling in the tumor cells is usually increased by autocrine and paracrine mechanisms and gives them a high growth potential, resistance to apoptosis, neoangiogenesis and metastasis, all essential parameters relevant for tumor progression. This makes FGFs, and their tyrosine kinase receptors FGFRs, valuable targets for therapeutic interventions. This book is a collection of 15 recent articles-both original work and reviews-that summarize the current research state effectively. The content covers FGF signaling aspects in gastric, skin, liver, esophageal cancer, melanoma, mesothelioma and glioblastoma, including one article that addresses the role of FGF in the tumor-microenvironment cross-talk. Several reports describe the development of compounds targeting FGFRs, their structure and interaction with the receptor molecules, and their effectivity in preclinical and clinical testing. In summary, the papers demonstrate the complexity of the topic, with various FGF ligands and receptors involved and the need for further research. They also present results that fuel hope that targeting cancer with dysfunctional FGF signaling can become a realistic treatment option.